Sidgwickian ethics - Phillips, David (David K.) (New York ; Oxford : Oxford University Press, 2011)
In this work David Phillips interprets and evaluates the central argument of the methods of ethics in a way that brings out the important conceptual and historical connections between Sidgwick's views and contemporary moral philosophy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Utilitarianism -- England -- History; Sidgwick, Henry, -- 1838-1900.